Do sagrado ao secular: a contribuição do saber médico para a construção dos cemitérios oitocentistas - Rodrigues, Caroline [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In 1832, the Faculties of Medicine head offices in Brazil were located at Salvador and Rio de Janeiro. The proximity of those societies with physicians led them to become a matter of observation and critical inquiries by those professionals. New physicians pondered about urban issues, particularly regarding burial ceremonies, that up to that moment were held inside of Catholic church temples. Behind such practice, there was a longstanding religious tradition, on the opposite way of the current medical outlook, that provided rules to be applied when individuals drew their last breath. Those funeral ceremonies practiced in Brazil were understood by physicians as a matter of public health, and for such reason, became part of their studies and personal concerns. In light of those events, this research aims to ponder about the reception of the medical discourse and which changes it was able to perform regarding the manner burials were carried out. From the analysis of medical writings, periodicals and legislation, we shall seek to understand the establishment of medical propositions that culminated in the building of the first cemeteries in hygienic patterns

Em 1832, as cidades de Salvador e do Rio de Janeiro tornam-se sedes das Faculdades de Medicina do Brasil. O contato dessas sociedades com os médicos coloca-as como alvo de seus olhares e críticas. Os novos médicos preocuparam-se com os problemas urbanos, em especial com os sepultamentos, que até então eram realizados no interior das igrejas. Por traz de tal prática havia uma longa tradição religiosa, que, na contramão da perspectiva médica, estabelecia as normas pelas quais os indivíduos deveriam proceder quando se encontravam com a morte. Os atos fúnebres presentes no Brasil foram entendidos por esses médicos como um problema de saúde publica, tornando-se, assim, parte de seus estudos e inquietações. Diante desse quadro o objetivo maior da presente pesquisa está em pensar como se deu a recepção do discurso médico e quais as alterações que esse conseguiu realizar nas vigentes formas de sepultar. Partindo da analise de escritos médicos, periódicos e legislações, buscaremos compreender o processo de instauração das propostas médicas que culminaram na construção dos primeiros cemitérios, nos moldes higiênicos
Keywords: História; Medicina social; Problemas sociais; Cemiterios - Aspectos religiosos - História - Brasil; História social - Séc. XIX